Robots - "Gifford, Clive" (Kingfisher, London, 2011)
Make science accessible with this essential series that will capture children's imagination while laying the foundation for future learning. With age-appropriate language and an eye-catching design, Discover Science gives young readers the answers to fundamental questions about the human body, animals, planet Earth and the Solar System